(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2026)
This paper analyzes the results of a study to begin in 2022 at various higher education institutions for teacher training in the province of Córdoba, as part of the final project for the Specialization in Social Sciences Education at the National University of Córdoba. The objective of this research was to identify the degree of visibility or invisibilization of afrodescendants in the history taught in elementary schools. The question that guided the empirical study was: what place do afrodescendants occupy as social actors in the argentinean history classes taught in elementary schools? For this purpose, we developed a fieldwork in which various qualitative techniques were combined, such as the analysis of the curricular design, questionnaires to students to identify their social representations, in-depth interviews to teachers at the higher level and to afrodescendant activists, as well as the participant observation of some history classes in the first year of the course.